ANALISIS EFISIENSI PEMUNGUTAN PENDAPATAN ASLI DAERAH MENGGUNAKAN DATA ENVELOPMENT ANALYSIS (DEA) STUDI PADA PEMERINTAH KABUPATEN ACEH BESAR - , Muharril Al Aqshar ([Yogyakarta] : Universitas Gadjah Mada, 2012)
he aim T s of this research are to analyze the collection efficiency of Local Owned Revenue (PAD) and to analyze the influences of the collection efficiency towards Locally Derived Revenue (PAD) at Local Government Unit of Work (SKPD) in the District Government of Aceh Besar that generate the revenue. Research period encompassed three years of observation from 2009 till 2011. Data Envelopment Analysis (DEA) was used to analyze the efficiency of collection, whereas a simple linear regression was used to analyze the influences of collection towards Locally Derived Revenue (PAD). s The results of this research by Data Envelopment Analysis (DEA) show that the Financial Management and Regional Property Agency was such an efficient and consistent SKPD in performing Local Owned Revenue (PAD) collection because SKPD was capable in achieving 100 percent of efficiency during the observation period. Road and Human Settlement Agency in 2011 is the inefficiency, but in 2009 until 2010 had achieved the relatively good performance, because in those years it was efficient in conducting Locally Derived Revenue (PAD) collection. While One Door Integrated Service Agency, Industry Trade and Cooperation of Small Medium Enterprises Agency, Transportation Communication and Telecommunication Agency, Culture Tourism Youth and Sport Agency, Agriculture and Food Crops Agency, Husbandry Agency, Marine and Fisheries Agency, and Public Hospital were not efficient in performing Locally Derived Revenue (PAD) collection during the years 2009 through 2011. The result of estimation the Simple Linear Regression shows the efficiency of collection has a positive and significant impact on Locally Derived Revenue (PAD), and it is able to explain the performance of Locally Derived Revenue (PAD) in the amount of 28.36 percent.